2016
DOI: 10.1371/journal.pgen.1005691
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Targeted Mouse Mutations Reveals the Topography of Local Changes in Gene Expression

Abstract: The unintended consequences of gene targeting in mouse models have not been thoroughly studied and a more systematic analysis is needed to understand the frequency and characteristics of off-target effects. Using RNA-seq, we evaluated targeted and neighboring gene expression in tissues from 44 homozygous mutants compared with C57BL/6N control mice. Two allele types were evaluated: 15 targeted trap mutations (TRAP); and 29 deletion alleles (DEL), usually a deletion between the translational start and the 3’ UTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 72 publications
1
41
0
Order By: Relevance
“…Insertion of foreign DNA fragments into the genome may have unintended effects on the expression and function of neighboring genes. In a recent study, West et al (15) have used RNA-seq to analyze in a systematic manner the transcriptional impact of targeted mouse mutations on local changes in gene expression. They measured the expression levels of genes within +/− 500 kb of the targeted gene in tissues from 44 homozygous mutants generated by the International Knockout Mouse Consortium (16) compared with C57BL/6N inbred control mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insertion of foreign DNA fragments into the genome may have unintended effects on the expression and function of neighboring genes. In a recent study, West et al (15) have used RNA-seq to analyze in a systematic manner the transcriptional impact of targeted mouse mutations on local changes in gene expression. They measured the expression levels of genes within +/− 500 kb of the targeted gene in tissues from 44 homozygous mutants generated by the International Knockout Mouse Consortium (16) compared with C57BL/6N inbred control mice.…”
Section: Resultsmentioning
confidence: 99%
“…The targeting strategies insert a bacterial beta-galactosidase reporter ( lacZ gene) downstream of the target gene endogenous promoter and a neomycin resistance selection cassette, similar to the strategy used to produce Mapk6 lacZ mutant mice. The authors found that one or more neighboring genes is down-regulated or up-regulated in up to 59% of the mouse mutants, depending on the targeting approach (15). Various mechanisms have been proposed to explain this local transcriptional dysregulation, including disruption of regulatory and insulating elements with cis-acting consequences and effects of the exogenous neo r promoter on expression of 3’ genes.…”
Section: Resultsmentioning
confidence: 99%
“…The conditional allele reported here removes exon 3 of Erk3 and leaves only a single FRT and a single loxP sites in intron 2. The insertion of a lacZ-neomycin-resistance-cassette often altered transcription of genes in the flanking DNA around the targeted gene, and accordingly the phenotype of the mutation (26-29). This may be due to the loss or disruption of intragenic regulatory elements, the constitutive promoter driving the neomycin gene, removal of insulating DNA in the targeted alleles, and local silencing due to disruption of normal chromatin organization by the exogenous construct (26).…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of a lacZ-neomycin-resistance-cassette often altered transcription of genes in the flanking DNA around the targeted gene, and accordingly the phenotype of the mutation (26-29). This may be due to the loss or disruption of intragenic regulatory elements, the constitutive promoter driving the neomycin gene, removal of insulating DNA in the targeted alleles, and local silencing due to disruption of normal chromatin organization by the exogenous construct (26). The detailed transcriptome analysis of 29 targeted alleles in mice revealed that down-regulated genes flanking the targets were rather equally distributed 5’ and 3’ of the target and the median distance from the target was 34kb (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation